Efficacy of two injection-site localisation techniques for botulinum toxin injections: a single-blind, crossover, randomised trial protocol among adults with hemiplegia due to stroke. Issue 11 (15th November 2016) - Morel, Claire; Hauret, Isabelle; Andant, Nicolas; Bonnin, Armand; Pereira, Bruno; Coudeyre, Emmanuel
Abstract : Introduction: Botulinum toxin injections are an effective treatment for limb spasticity following stroke. Different tracking techniques are used for this purpose: palpation, electrostimulation, electromyography and ultrasound. Yet very few studies have compared these different techniques, and none has successfully proved the superior efficacy of ultrasound-guided injections compared to another tracking method. The primary objective of our study was therefore to compare the efficacy of botulinum toxin injections depending on the tracking technique used: ultrasound versus electrostimulation. Methods and analysis: This is a clinical, single-centre, prospective, interventional, single-blind, crossover, randomised trial. In total, 30 patients aged between 18 and 80 years presenting with triceps surae spasticity (evaluated >1 on the modified Ashworth scale) associated with hemiplegia sequelae due to stroke will be included. The patients will be selected among those who attend for consultation the Physical Medicine and Rehabilitation Department of the Clermont-Ferrand University Hospital. One group will receive the abobotulinumtoxinA (BoNT-A) injection guided by electrostimulation then ultrasound, and the second group's botulinum toxin injections will be guided by ultrasound then electrostimulation. For each patient, the duration of study participation is 5 months. The primary end point is variation in passive ankle dorsiflexion range of motion at slow and high speeds (Tardieu scale) with the knee straight. Ethics and dissemination: This study received ethics approval form the CPP of Rhônes-Alpes region. Results will be published in a peer-reviewed journal. Trial registration number: NCT01935544; pre-results.